2021
DOI: 10.1186/s12884-021-03591-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences are associated with illicit drug use among pregnant women with middle to high socioeconomic status: findings from the All Our Families Cohort

Abstract: Background Adverse childhood experiences (ACEs) are associated with illicit drug use among pregnant women who are socioeconomically vulnerable. While it is assumed that the impact of ACEs on illicit drug use in pregnancy is reduced among women with higher socioeconomic status (SES), this assumption is not well tested in the literature. The objective of this study was to examine the impact of maternal ACEs on illicit drug use in a community-based sample of pregnant women with middle to high SES.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
1
12
2
3
Order By: Relevance
“…The copyright holder for this preprint this version posted July 29, 2021. ; https://doi.org/10.1101/2021.07.23.21261027 doi: medRxiv preprint Prenatal illicit drug use was present in 6% of the study sample which is comparable to other ACE studies involving a cohort of pregnant women residing in HIC (3.1%) (see Racine et al, 2018). Multilevel logistic regressions suggested that, more broadly, there is low probability of prenatal illicit drug use across the different classes; these findings are inconsistent with previous research that suggest a dose-response relationship between maternal ACEs and prenatal illicit drug use (Currie & Tough, 2021). However, the pairwise differences between classes suggest that the highly maltreated class and the emotionally abused class, but not the intra-familial violence exposed class, had greater probability of prenatal illicit drug use compared to the normative class.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted July 29, 2021. ; https://doi.org/10.1101/2021.07.23.21261027 doi: medRxiv preprint Prenatal illicit drug use was present in 6% of the study sample which is comparable to other ACE studies involving a cohort of pregnant women residing in HIC (3.1%) (see Racine et al, 2018). Multilevel logistic regressions suggested that, more broadly, there is low probability of prenatal illicit drug use across the different classes; these findings are inconsistent with previous research that suggest a dose-response relationship between maternal ACEs and prenatal illicit drug use (Currie & Tough, 2021). However, the pairwise differences between classes suggest that the highly maltreated class and the emotionally abused class, but not the intra-familial violence exposed class, had greater probability of prenatal illicit drug use compared to the normative class.…”
Section: Discussioncontrasting
confidence: 96%
“…The findings suggested high prevalence and co-occurrence of maternal ACEs in this cohort, with 39% having experienced ≥ 4 ACEs which is higher compared to other ACE studies involving a cohort of pregnant women in HICs (14.1% and 14.7%, respectively). (see Currie & Tough, 2021). A model with four distinct latent classes was judged optimal for these data, with classes labelled: the highly maltreated class (7%), the emotionally and physically abused with intra-familial violence exposure class (13%), the emotionally abused class (40%), and the low household dysfunction and abuse class (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Associations were adjusted for covariates selected a priori from the literature including age, marital status, the number of children a participant had, and their current adult income group (Kajeepeta et al, 2015). Mental health and health behaviour covariates were not included in models given the impacts of childhood trauma on mental health and behaviour are well documented across studies (Afifi et al, 2014;Currie, 2006;Currie & Tough, 2021;Petersen et al, 2014). Thus, controlling for mental health variables, which likely sit on the causal pathway between child abuse and adult sleep, would result in biased estimates.…”
Section: Statistical Approachmentioning
confidence: 99%
“…Using the Evidence for Better Lives Study (EBLS) dataset, the number and characterizations of latent ACEs and their associations with prenatal substance use and poor infant outcomes were explored. The findings suggested high prevalence and co-occurrence of maternal ACEs in this cohort, with 39% having experienced ≥ 4 ACEs which is higher than in ACE studies involving pregnant women in HICs [ 29 ].…”
Section: Discussionmentioning
confidence: 86%